Determining the Effects of Earthquakes through Comments on Social Forums - Mungen, Ahmet Anil; Kaya, Mehmet (Institute of Electrical and Electronics Engineers Inc., 2020)
The natural phenomena of the earth have always take to people's attention. People may have to change the flow of the day because of these unexpected events that are outside of the daily routine. Internet users regularly share their opinions and comments on daily events on the Internet. Along with social networks, forum sites such as Reddit have also been the leading areas where users share their comments. Turkey has very active seismic zone. Ever year dozens of earth active seen in Turkey. There are an average of 3 medium-sized earthquakes each year caused by these faults. In this study correlation between the reactions of internet users to earthquakes was investigated and found important reasons likes media effects. Thus, it has been tried to find the relationship between the effects of the earthquake on people and the actual scale beside the earthquake zone. © 2020 IEEE.
2020 International Conference on Data Analytics for Business and Industry: Way Towards a Sustainable Economy, ICDABI 2020 -- 26 October 2020 through 27 October 2020 -- Sakheer -- 166670
Keywords: blogs; earthquake; emotional analysis